Análise geoecológica e gestão ambiental no campo de dunas do Mundaú - Trairi (CE) - Brito, Maevy dos Santos (2024)
The purpose of this research is to understand the natural landscape dynamics in the dune field in the district of Mundaú in the municipality of Trairi, located on the west coast of the state of Ceará. Its relevance arises from the need to develop research focused on environmental management so that more appropriate management can be developed for each type of coastal environment. Based on this, analyzing these areas is fundamental to this and it is in the meantime that the scope of the research is formed. The general objective is to understand the natural landscape dynamics of the Mundaú dune field, taking into account the evolutionary and dynamic aspects that make it dynamic from the perspective of Landscape Geoecology. The specific objectives are: identifying and characterizing the geoecological units that interact with the Mundaú dune fields; characterize the typologies of the set of geomorphological features existing in the dune field and; prepare environmental management proposals for the area. Thus, the research aims to answer some questions associated with the analyzed context, namely: What is the current diagnosis of the geoecological units in the area? What geomorphological typologies prevail in the Mundaú dune field? Can a diagnosis of integrated analysis of these units and the flows of matter and energy that form the region's landscape help in local environmental and social management? A management proposal for the study area can generate input for the environmental planning of the dune field, delimiting important areas, analyzing the limitations, exploring the potential of this landscape subunit, evaluating the current and possible environmental impacts, in order to promote the sustainable development of the region? To this end, a survey and analysis of the geoecological components that constitute the landscape of the dune field was carried out, regarding geology, pedology, hydrography, vegetation cover, climate and geomorphology. As well as the characterization of the area's geoecological units, based on the integration of environmental elements and land use and occupation, which resulted in proposals for eight zonings in the Mundaú district. Finally, strategies aimed at Environmental Education were also proposed, with the aim of its practice in Non-Governmental Organizations and local schools.